PENDIDIKAN ISLAM DAN KECERDASAN MAJEMUK (MULTIPLE INTELLIGENCE) - Risydah Fadilah (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Education is guidance or help given by educators to the development of students to reach maturity with the aim that children are capable enough to carry out their own life tasks not with the help of others. The purpose of education is to create a person of high quality and character so that he has a broad view of the future to achieve the goals that are expected and able to adapt quickly and precisely in various environments. The educational objectives will be achieved if done with the teaching and learning processboth in the school environment or elsewhere. Learning is one of the activities or human endeavors that is very important and must be carried out throughout life, because through the effort of learning we can make changes or improvements in various matters that concern our self-interest. Learning is done intentionally or not with the teacher, with the help of others, or without anyone's help. The measurement of success, to the potential possessed, to the process of change always departs from experience whether it is research or theories that have been prepared previously. As is the case with human success there are those who see it from the intelligence of their brains (intelligence) or also their work skills. Intelligence is often interpreted as the ability to understand thingsand the ability to think. Intelligence in this sense is usually measured by the ability to answer standardized test questions in the classroom (IQ test). However the glorification of IQ in determining success still dominates learning in schools and one of them appears in the use of traditional learning methods, such as lectures and stories that are more inline with linguistic intelligence and rational approaches to mathematical logic that are more in line with logical mathematical intelligence. Even Islamic Religious Education  (PAI) learning is still mostly filled with memorization, ritual worship practices, religious dogmas and the like, to the point of unattractive, boring and less meaningful for studentswhose linguistic and mathematical intelligence is less prominent. Students can only study well if the material is delivered using methods that are in accordance with their most prominent intelligence. The types of intelligence incorporated in 9 multiple intelligences or Multiple Intelligence are: Linguistic Intelligence, Mathematical Logic Intelligence, Spatial Intelligence, Body Kinesthetic Intelligence, Musical Intelligence, Interpersonal Intelligence, Intrersonal Intelligence, Natural Intelligence, and Existential Intelligence. Compound intelligence in the view of Islam is explained in the ESQ book from Ari Ginanjar Brain Gym or Brain Gym can be done to improve the work performance of thebrain.Keywords: Education, Learning, Intelligence and Multiple Intelligence, Brain Gym.